1130 Describing the evolution in the ethics education provided by a Paediatric Bioethics Centre (PBC) before and during the pandemic. (17th August 2022) - Dittborn, Mariana; Brierley, Joe
Abstract : Aims: One important PBC function is to provide ethics education for members, hospital staff & other students. Educational activities are open to national and international healthcare students and workers. No standardised guidance exists Re how to run or evaluate such activities, though national UKCEN core competencies provide an ethics curriculum. The objective of this work is to describe the evolution of PBC educational activities over the pandemic period 2019-22. Methods: PBC educational activities database review: Results: The PBC provides training to its members, hospital staff, trainees and students, as well as external educational activities. These include: PBC members - monthly 1-hour Bioethics Educational Forum with local/regional speakers evolved with videoconferencing to involve national/international speakers. Similarly, annual PBC Away Day now has more international speakers with positive feedback, tempered slightly by loss of team bonding. Each (of 10) new associate-member presents at bespoke 1-hour monthly online sessions, supported by mentor, unchanged by pandemic. Hospital staff, trainees & students – vary in methods and scope, i.e., standalone sessions and ethics/law lectures embedded in other courses. e.g., 8 Weekly Autumn ethics interactive lectures open to hospital AND sessions on request to tackle moral injury. Feedback surprisingly positive, though efficacy not formally assessed. External educational activities - include annual Medical Student Bioethics Day with lectures, workshops & abstract presentations; a one-week Paediatric Ethics & Law MSc Module and ad-hoc seminars/conferences to address timely hot topics (i.e., 2019 ' Recent Court Judgements: should we change clinical practice?' & 2020 'Role of Faith & Non in Society's Pandemic Emergence' ) Again, broader speaker pool facilitated, very positive feedback scores maintained online. The pandemic brought both challenge and opportunity. Educational activities were adapted to the online format, raising concerns about the loss of face-to-face discussion and interaction. However, videoconferencing allowed greater participation of national/international ethics experts and delegates. Informal and formal feedback from participants was entirely positive regarding the change; however, educators found entire day sessions arduous– these evolved to shorter sessions/fewer per teacher. Conclusion: Remote learning offers new opportunities for ethics education/training activities. Further work should be done to evaluate not just participants' and educators' experience but to compare the efficacy of different modes of training.